Percutaneous Coronary Interventions in Chronic Total Occlusion - Profile, Technique and Outcome - The Malabar Experience - Vinayakumar, Desabandhu (Journal of the Saudi Heart Association, 2020)
© 2020 Saudi Heart Association.